2018
DOI: 10.3390/ijerph15102220
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Organic Loading Rate on Anaerobic Digestion Performance of Mesophilic (UASB) Reactor Using Cattle Slaughterhouse Wastewater as Substrate

Abstract: In this study, the performance of a laboratory scale upflow anaerobic sludge blanket (UASB) reactor operating at mesophilic temperature (35 °C) was examined. Cattle slaughterhouse wastewater (CSWW) was used as the main substrate. The total and effective volumes of the reactor were 8 L and 6 L, respectively. Twelve different organic loading rates (OLR) were applied and the performance was evaluated. The chemical oxygen demand (COD) removal efficiency was more than 90% during batch study. In the continuous study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
32
1
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 81 publications
(45 citation statements)
references
References 43 publications
6
32
1
6
Order By: Relevance
“…Compared with the acidosis events in the aforementioned works from Goux et al (2015) and Musa et al (2018), it appears that the OLR in the present study (max. 2.72 gVS L −1 d −1 ) was still too small to cause acidosis.…”
Section: Chemical Parameterscontrasting
confidence: 64%
See 1 more Smart Citation
“…Compared with the acidosis events in the aforementioned works from Goux et al (2015) and Musa et al (2018), it appears that the OLR in the present study (max. 2.72 gVS L −1 d −1 ) was still too small to cause acidosis.…”
Section: Chemical Parameterscontrasting
confidence: 64%
“…In an experiment by Goux et al (2015), where the OLR was gradually increased, acidosis took place approximately at 4 gVS L −1 d −1 . In a recent study by Musa et al (2018), an UASB reactor showed an even higher stability compared with that of Goux et al (2015), as the OLR was increased until 15 gCOD L −1 d −1 before acidosis took place. In the study presented here, the loading rate in the reactor receiving sodium phosphate was based on the works from Goux et al and Musa et al, and an OLR of 1.29 gVS L −1 d −1 , not close to a range that could cause acidosis.…”
Section: Chemical Parametersmentioning
confidence: 96%
“…It includes chemical coagulation, lagoon pond systems, sedimentation and filtration, adsorption, chlorination, and high rate oxidation ditches [14]. These methods produce high-quality effluent, however, the large area space requirement for plant installation, huge sludge production, high energy demand, offensive odor, lack of energy recovery, and the overall cost of operation and maintenance have been reported as the major drawback [19]. Due to pressure from environmentally aware consumers, various guidelines and water quality criteria have been set by both local and international committees.…”
Section: Introductionmentioning
confidence: 99%
“…A functional anaerobic digestion system depends on the buffering capacity and the degree of adaptation of the microorganisms [19]. The high protein and lipid content of slaughterhouse wastewater makes it a challenging substrate for degradation by the microbial consortium.…”
Section: Phmentioning
confidence: 99%
“…Moreover, the condition at which the UASB reactor operates plays a vital role in the performance of the bioreactor. For instance, the study of Musa et al [19] on SWW treatment under mesophilic temperature (35 • C) revealed a COD removal efficiency of 70% at an organic loading rate of 10 g L −1 day −1 . Similarly, Mittal et al [20] reported a UASB reactor with an average COD removal efficiency of 80-85% and is very much efficient when operated at an organic loading rate (OLR) of 2.7-10.8 kg COD m −3 day −1 .…”
Section: Introductionmentioning
confidence: 99%